2020
DOI: 10.1111/cbdd.13677
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death ligand‐1: A dynamic immune checkpoint in cancer therapy

Abstract: Antibody-based immunotherapies play a pivotal role in cancer research with efficient achievements in tumor suppression. Tumor survival is assisted by modulation of immune checkpoints to create imbalances between immune cells and cancer cell's environment. The modulation results in T-cell signal inhibition ultimately inert its proliferation and activation against various tumor cells. PD-L1, a 40 kDa transmembrane protein of B7 family, binds with PD-1 on the membrane of T cells which results in inhibition of T-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 114 publications
(148 reference statements)
0
16
0
Order By: Relevance
“…The present results suggested that miR-142 was downregulated in LAd, and the overexpression of miR-142 contributed to chemosensitivity in ddP-resistant LAd cells. Pd-L1 may promote tumor cell proliferation and differentiation by creating an imbalance between immune cells and the cellular environment (28,29). Pd-L1 is also reported to be involved in the regulation of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…The present results suggested that miR-142 was downregulated in LAd, and the overexpression of miR-142 contributed to chemosensitivity in ddP-resistant LAd cells. Pd-L1 may promote tumor cell proliferation and differentiation by creating an imbalance between immune cells and the cellular environment (28,29). Pd-L1 is also reported to be involved in the regulation of tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the interaction between PD-1 and PD-L1 is a key therapeutic target for reactivating the immune response against a variety of cancers. Therefore, blocking the PD-1/PD-L1 interaction with an antibody against the PD-L1 molecule is a new therapeutic opportunity for patients with advanced platinum-resistant ovarian cancer (102)(103)(104). The human immunoglobulin G1 monoclonal antibody avelumab has a wild-type Fc region that blocks PD-L1.…”
Section: Cancer Stem Cells (Cscs) the Current Oncology Hypothesismentioning
confidence: 99%
“…Immune check point proteins such as PD-1 are targeted for restoration of anti-HBV immune response breaking immune tolerance. Preclinically, the combination of an antibody to the PD-1 ligand (programmed death ligand 1) [129] with DNA vaccination resulted in complete viral clearance in a woodchuck model [130], successfully supporting the therapeutic potential of restored T cell response [131]. Indeed, blockade of PD-1 has been shown to partially restore HBV-specific T cell function [126 •• ].…”
Section: Immune-mediated Degradation Of Cccdnamentioning
confidence: 99%